Design of Inward-Turning External Compression Supersonic Inlet for Supersonic Transport Aircraft - Muhammad Adnan Utomo; Romie Oktavianus Bura (INSIST, 2017)
Inward-turning external compression intake is one of the hybrid intakes that employs both external and internal compression intakes principle. This intake is commonly developed for hypersonic flight due to its efficiency and utilizing fewer shockwaves that generate heat. Since this intake employ less shockwaves, this design can be applied for low supersonic (Mach 1.4 - 2.5) intakes to reduce noise generated from the shockwaves while maintaining the efficiency. Other than developing the design method, a tool is written in MATLAB language to generate the intake shape automatically based on the desired design requirement. To investigate the intake design tool code and the performance of the generated intake shape, some CFD simulation were performed. The intake design tool code can be validated by comparing the shockwave location and the air properties in every intake's stations. The performance parameters that being observed are the intake efficiency, flow distortion level at the engine face, and the noise level generated by the shockwaves. The design tool written in MATLAB is working as intended. Two dimensional axisymmetric CFD simulations validation has been done and the design meets the minimum requirement. As for the 3D inlet geometry, with a little modification on diffuser and equipping vent to release the buildup pressure, the inlet has been successfully met the military standard on inlet performance (MIL-E-5007D). This design method also has feature to fit every possible throat cross sectional shapes and has been proven to work as designed.Keywords— Inward-turning, Supersonic, Engine Intakes, Low- noise, Design Method